Technique and Results of Biliary Reconstruction Using Side-to-Side Choledochocholedochostomy in 300 Orthotopic Liver Transplants - Neuhaus, Peter; Blumhardt, Gerhard; Bechstein, Wolf O.; Steffen, Rudolf; Platz, Klaus-Peter; Keck, Heinrich (Annals of surgery, 1994)
The authors evaluated the complication rate and outcome of side-to-side common bile duct anastomosis after human orthotopic liver transplantation. Early and late biliary tract complications after orthotopic liver transplantation remain a serious problem, leading to increased morbidity and mortality. Commonly performed techniques are the end-to-end choledochocholedochostomy and the choledochojejunostomy. Both techniques are known to coincide with a high incidence of leakage and stenosis of the bile duct anastomosis. The side-to-side bile duct anastomosis has been shown experimentally to be superior to the end-to-end anastomosis. The authors present the results of 316 human liver transplants, in which a side-to-side choledochocholedochostomy was performed. Biliary tract complications of 370 transplants in 340 patients were evaluated. Three hundred patients received primary liver transplants with side-to-side anastomosis of donor and recipient common bile duct. Thirty-two patients with biliary tract pathology received a bilioenteric anastomosis, and in eight patients, side-to-side anastomosis was not performed for various reasons. Clinical and laboratory investigations were carried out at prospectively fixed time points. X-ray cholangiography was performed routinely in all patients on postoperative days (PODs) 5 and 42. In patients with suspected papillary stenosis, endoscopic retrograde cholangioscopy and papillotomy were performed. One biliary leakage (0.3%) was observed within the early postoperative period (PODs 0 through 30) after liver transplantation. No stenosis of the common bile duct anastomosis was observed during this time. Late biliary stenosis occurred in two patients (0.6%). T tube-related complications were observed in 4 of 300 primary transplants (1.3%). Complications unrelated to the surgical technique, including papillary stenosis (5.7%) and ischemic-type biliary lesion (3.0%), which must be considered more serious in nature than complications of the anastomosis or T tube-related complications, were observed. Papillary stenosis led to frequent endoscopic interventions and retransplantations in 1.3%. Side-to-side common bile duct anastomosis represents a safe technique of bile duct reconstruction and leads to a low technical complication rate after human orthotopic liver transplantation. Ischemic-type biliary lesion evoked by preservation injury, arterial ischemia, cholestasis, and cholangitis may represent a new entity of biliary complication, which markedly increases the morbidity after human liver transplantation. Therefore, this complication should be the subject of further research.